Blood coagulation and fibrinolysis in aortic valve stenosis: links with inflammation and calcification - Natorska, Joanna; Undas, Anetta (Thrombosis and Haemostasis, 2015)
Aortic valve stenosis (AS) increasingly afflicts our aging population. However, the pathobiology of the disease is still poorly understood and there is no effective pharmacotherapy for treating those at risk for clinical progression. The progression of AS involves complex inflammatory and fibroproliferative processes that resemble to some extent atherosclerosis. Accumulating evidence indicates that several coagulation proteins and its inhibitors, including tissue factor, tissue factor pathway inhibitor, prothrombin, factor XIII, von Willebrand factor, display increased expression within aortic stenotic valves, predominantly on macrophages and myofibroblasts around calcified areas. Systemic impaired fibrinolysis, along with increased plasma and valvular expression of plasminogen activator inhibitor-1, has also been observed in patients with AS in association with the severity of the disease. There is an extensive cross-talk between inflammation and coagulation in stenotic valve tissue which contributes to the calcification and mineralisation of the aortic valve leaflets. This review summarises the available data on blood coagulation and fibrinolysis in AS with the emphasis on their interactions with inflammation and calcification.
Keywords: Aortic stenosis; blood coagulation; fibrinolysis; fibrin; tissue factor